Glass slippers, ever after and me [large type] - Wright, Julie, 1972- (Proper romance., 2020)
"When aspiring author Charlotte Kingsley finally gets published, she thinks all her dreams have come true. But the trouble begins when her publicity firm reinvents her quirky online presence into a perfectly curated dream life. Gone are the days of sweatpant posts and ice cream binges with her best friend, Anders, replaced instead with beautiful clothes, orchestrated selfies, and no boyfriend. Only, that carefully curated fairy tale life is ruining her self-esteem and making her feel like a fraud. When a bestselling author takes Charlotte under her wing--almost like a fairy godmother--she helps Charlotte see the beautiful person she already is and the worth of being authentic. But is it too late to save her relationship with Anders? The clock is quickly ticking towards midnight, and Charlotte must decide between her fairy tale life and the man she loves, before he's gone forever"--